Prevalence of vision loss in South and Central Asia in 2020: magnitude and temporal trends - Nangia, Vinay; Jonas, Jost B. (Ophthalmic epidemiology, 2024)
To estimate the prevalence of vision loss for 2020 in South and Central Asia and analyze trends since 1990. In a systematic literature review, we estimated the prevalence of blindness, visual impairment (VI) and presbyopia-related VI in 1990,2000,2010, and 2020. The study included 103 population-based studies. In South/Central Asia combined, age-standardized prevalence of blindness, moderate-to-severe VI (MSVI), moderate VI, severe VI, mild VI and presbyopia-related VI for all ages was 0.65% (95% uncertainty interval (UI):0.56/0.74), 5.06 (4.55/5.59), 4.40 (3.91/4.94), 0.65 (0.57/0.74), 3.21 (2.89/3.56), and 8.77 (6.37/11.48), respectively, with higher values for women than men. From 2000 to 2020, changes in age-standardized prevalence in South Asia were −36.85 (−36.94/−36.76), −7.01 (−7.13/−6.90), −5.86 (−5.99/−5.73), −13.96 (−14.09/−13.82), −9.55 (−9.66/−9.44), and −8.62 (−8.93/−8.31), respectively for men, and −38.50 (−38.59/−38.40), −10.12 (−10.22/−10.01), −9.23(−9.36/−9.10), −14.86 (−14.99/−14.73), −9.44 (−9.56/−9.33), and −7.78 (−8.09/−7.48), respectively for women. From 2000/2020, the changes in age-standardized prevalence figures in Central Asia were −21.44 (−21.58/−21.30), −2.75 (−2.87/−2.64), −2.17 (−2.30/−2.04), −7.12 (−7.26/−6.99), −5.36 (−5.48/−5.25), and −3.67(−4.02/−3.32), respectively for men, and −21.13 (−21.27/−20.99), −2.70 (−2.81/−2.58), −2.18 (−2.30/−2.05), −6.93 (−7.07/−6.80), −5.03 (−5.14/−4.91), and −2.65 (−3.00/−2.30), respectively, for women. In 2020, 11.94 million (9.98-14.07) and 0.30 million (0.24-0.36) individuals were blind, and 96.22 million (84.12-110.27) and 2.95 million (2.52-3.43) had MSVI in South Asia and Central Asia, respectively. Despite a higher decrease between 2000 and 2020, the age-standardized prevalence of blindness and MSVI were higher in South Asia than in Central Asia in 2020. The number of people affected increased due to population growth and improved longevity.
Mitglieder der GBD 2019 Blindness and Vision Impairment Collaborators & Vision Loss Expert Group of the Global Burden of Disease Study: Vinay Nangia, Prof Jost B Jonas, Arthur G Fernandes, Ian Tapply, Maria Vittoria Cicinelli, Alessandro Arrigo, Paul Svitil Briant, Prof Theo Vos, Prof Serge Resnikoff, Prof Hugh R Taylor [und viele weitere...]
Gesehen am 31.03.2025